Mini Food Waste Composter Machine - Muhammad Nazry, Uzma Nur Huda; Mohd Jufri, Nurul Hanis; Khairussalih, Nurain Saliha; Othman, Muhammad Azri; Mohamad Ismail, Mohamad Razif (Multidisciplinary Applied Research and Innovation, 2026)
Food waste is a major environmental problem that contributes to greenhouse gas emissions and causes landfill overflow. In Malaysia, poor waste management at home leads to traditional harmful disposal methods like dumping and burning. In other hand, composting presents a sustainable solution by turning organic waste into nutrient-rich fertilizer; however, traditional composting methods is timely and require a lot of effort. This project aims to create a Mini Food Waste Composter Machine that automates the shredding and mixing processes for small users such as households and small cafes. The system combines mechanical, electrical, and control parts with a MOTION 2350 Pro microcontroller, a stainless-steel shredder, and a static mixer to enhance the composting process. Evaluation tests with 300 grams of food waste showed that soft waste was completely processed in 20 to 30 seconds, while fibrous waste took longer. While full automation was not achievable due to mechanical constraints, the semi-automated system worked well. In conclusion, this project offers a practical, low-cost, and sustainable solution for managing organic waste on a small scale.